Readymade Code: Braille in Contemporary Visual Culture - Vanessa Warne (Disability Studies Quarterly, 2018)
This essay examines the proliferation of enlarged braille as a design element in contemporary culture. Exploring the relationship between the enlargement of braille and the use of braille as a code, I explore the cultural appropriation of braille by sighted creators who are not interested in blind people's reading and writing experiences but who value instead the temporary obfuscation of written messages created for sighted people. The essay also discusses two art installations noteworthy for their tactical use of enlarged braille to critique the ocularcentrism of contemporary culture, a culture that is actively repurposing braille as a puzzle for sighted people to solve.